FUTURE ENGINEERS IN A DIGITAL EDUCATIONAL ENVIRONMENT PROFESSIONAL IMPROVING COMPETENCES (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article identifies the tasks of increasing the professional competencies of future engineers in the digital educational environment of Uzbekistan oath increasing the professional competencies of engineers in the digital educational environment in technical universities.
Keywords: digital education, professional competence, competence, modular training.